PENGARUH STRATEGI BISNIS PERUSAHAAN TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR MAKANAN DAN MINUMAN DI BURSA EFEK INDONESIA - Fathorrahman Fathorrahman; syaiful syaiful (J-MACC, 2019)
Indonesia is a legal state. All actions taken by each legal subject must be in accordance with applicable and legal law. Regarding the issue of special state administration regarding state revenue also regulated in the law. In the implementation of a sovereign state, national development is needed in stages, directed, sustainable and sustainable in all sectors, both physical and non-physical development. Population retrieval in this study is a number of manufacturing companies engaged in food and beverages that have been listed on the Indonesian stock exchange (IDX) in the period 2012-2015, which amounted to 14 companies. Every company taken is a company that has complete financial statement data in a row during the period 2012-2015. The sample of this study was taken using a purposive sampling technique, namely the selection of sample members based on certain criteria so that a sample of 8 companies was obtained. The analytical tool used in this study is multiple linear regression. Based on this research, partially or simultaneously there is no influence between marketing and sales, the growth rate of the company towards the level of tax avoidance.